Long-term exposure to commercially available sunscreens containing nanoparticles of TiO2 and ZnO revealed no biological impact in a hairless mouse model. Issue 1 (December 2015) - Osmond-McLeod, Megan; Oytam, Yalchin; Rowe, Anthony; Sobhanmanesh, Fariborz; Greenoak, Gavin; Kirby, Jason; McInnes, Elizabeth; McCall, Maxine
Abstract Background The application of sunscreen is a critical component of a sun-safe strategy, however the possibility of unexpected, adverse outcomes resulting from long-term use of sunscreens containing nanoparticles of titanium dioxide (TiO2 ) and zinc oxide (ZnO) has not yet been examined. Here, immune-competent hairless mice were exposed over a 36-week period to weekly topical applications of sunscreens containing nanoparticles of ZnO or TiO2, or no metal oxide nanoparticles, with or without subsequent exposure to ultraviolet radiation (UVR). Control groups received no sunscreen applications, with or without UVR. Results Mice exposed to UVR in the absence of sunscreen developed statistically significant incidences of histologically-diagnosed malignant and benign skin neoplasms, whereas no statistically significant adverse biological outcomes were found in mice treated with the sunscreens containing ZnO or TiO2 nanoparticles. Elevated levels of Ti were detected in the livers of mice treated with sunscreen containing TiO2 nanoparticles compared to untreated control, but total Zn concentrations did not significantly alter in any major organs except for the skin of mice treated with ZnO sunscreen. Exposure to UVR did not have a significant impact on examined tissue concentrations of Zn or Ti. Few to no transcriptional changes were found in ZnO or TiO2 -treated groups, but mice treated with the sunscreen containing only organic filters showed substantial gene disregulation. Conclusions Taken together with previous work, this long-term study provided no basis to avoid the use of sunscreens containing metal oxide nanoparticles.